NK Cells in the Pathogenesis of Chronic Obstructive Pulmonary Disease - Rao, Yafei; Le, Yanqing; Xiong, Jing; Pei, Yuqiang; Sun, Yongchang (Frontiers in Immunology, 2021)
Chronic obstructive pulmonary disease (COPD) is a prevalent chronic airway disease with varied frequencies of acute exacerbations, which are the main cause of morbidity and mortality of the disease. It is, therefore, urgent to develop novel therapies for COPD and its exacerbations, which rely heavily on understanding of the pathogenesis and investigation for potential targets. Current evidence indicates that natural killer (NK) cells play important roles in the pathological processes of COPD. Although novel data are revealing the significance of NK cells in maintaining immune system homeostasis and their involvement in pathogenesis of COPD, the specific mechanisms are largely unknown. Specific and in-depth studies elucidating the underlying mechanisms are therefore needed. In this review, we provided a brief overview of the biology of NK cells, from its development to receptors and functions, and outlined their subsets in peripheral blood and lungs. Then we reviewed published findings highlighting the important roles played by NK cells in COPD and its exacerbations, with a view of providing the current state of knowledge in this area to facilitate related in-depth research.